Socio-Economic Drivers of Climate Change Perception in Metropolitan Cities of Sub-Saharan Africa - Tongo, Samuel Osayamen; Dada, Olanrewaju Timothy; Odunsi, Oluwafemi Michael; Oladimeji, Sobowale Tolulope; Uzzi, Festus Osarumwense (NIU Journal of Social Sciences, 2023)
This research used the metropolitan cities of Kano and Lagos in Nigeria to assess socio-economic variables that drive the perception of the two broad classes of climate change beliefs: "climate change is real" and "humans cause climate change." The multistage sampling technique was used to respectively select 134 and 278 respondents across the different neighbourhoods in Kano and Lagos metropolises. Uniformly in Kano and Lagos metropolises, beliefs in climate change reality and the human cause were influenced by residents' age, parental status, and level of education. Anthropogenic climate sceptics were strongly influenced by ethnicity in both Kano and Lagos metropolises. While Muslim-dominated Kano mostly believes climate change is occurring but not caused by human activity, the Christian-dominated Lagos believes in climate change's reality and human cause. The results can assist the government in knowing how to embark on enlightenment and environmental education where all socio-economic status will be captured. Keywords: Climate Change, Perception, Beliefs, Socio-Economics, Ill-health, Nigeria